Effect of Science Teachers’ Knowledge, Attitudes and Skills on Out-Door Instruction, At Selected Secondary Schools in Uasin-Gishu County, Kenya - Kabesa, Stella (International Journal of Educational Studies, 2018)
Outdoor learning usually refers to organized learning that takes place outside the confines of a classroom. This study aims to empirically examine the effects of teachers‘ knowledge, attitude and skills on out-door instruction in Kenya. The study adapted a survey research design. A sample of 135 teachers was randomly obtained from a population of 318 teachers. The response rate was 77.59 per cent. Data was collected using both closed and open ended questionnaires. Data was analyzed by employing descriptive statistics, Pearson correlation and multiple regression analysis. The findings revealed that teachers‘ Knowledge, Attitude and Skills (KAS) are positively associated with out-of-classroom instruction in Kenya. The generalizability of the findings is limited as the study focused only in Kenya. Based on the findings, the study recommends that schools should focus on encouraging development of knowledge, attitude and skills in teachers thus promoting the use of out-door instruction in science. This study contributes to the theoretical and practical knowledge by providing the evidence about factors affecting science teaching. It is also expected to extend the knowledge on out-door learning.